Kebiasaan Makan Kerang Kepah (Polymesoda erosa) di Kawasan Mangrove Pantai Pasir Padi - Melinda, Mery; Sari, Suci Puspita; Rosalina, Dwi (OSEATEK, 2015)
Kerang kepah is a type of bivalves are commonly found in coastal mangroves areas Pasir Padi beach. Analysis of food habits can give an idea of the role of this species in the waters, and to know that there is a natural food resources in the waters. This aims of this study analyze food and abundance of kerang kepah. The research was conducted in July 2014. The determination of the station done by Purposive random sampling method.. Kerang kepah were taken from three stations by used transects measuring 1x1 meters squared distance between transects is 10 meters. The results of the analysis in the stomach and intestines kerang kepah, it can be concluded that the main meal in the form of phytoplankton as a natural food in the water as well as a group that plays an important role in aquatic ecosystems and can perform photosynthesis, while the food detritus complementary, IP value in the stomach 75.39% in the form of plankton and 24.62 form detritus, IP value in the instestinesl 75.50% in the form of plankton and 24.5 form detritus. Abundance of kerang kepah on the station I of 3 ind/25 m2, station II 1.75 ind/25 m2 and the station III 2 ind/25 m2. Differences in abundance values for each station were allegedly due to differences in the characteristics of each station.Keywords: Kerang kepah, Food Habits, Mangrove, Pasir Padi Beach